ELECTRONIC FOUNDS TRANSFER – EFT - Milorad M. Bejatović; Maja S. Kovačević (Pravo, 2009)
Electronic business and electronic trade as its component are new phenomena in modern business, exactly in the fields of trade, law, business relationships between individuals themselves, then between individuals and commercial organizations, and most of all between banks themselves as well as between banks and their clients. The phenomena such as: electronic signatures, electronic exchange of information, electronic way of paying, home banking, virtual shops and buying things through the Internet as well as making contracts and other most different kinds of business done through the Internet and other phenomena have contributed to the speed, quality and quantity of the done business transactions and all that with less expenses. As every other kind of business relationship, this one has also its defects coming from the fact that it is a new and not completely legally regulated area with numerous lacks especially in national legislatures. The safety of business transactions themselves could be endangered in different ways according to the fact that we are talking about doing some business through the WWW address. The law has been made in accordance with modern principles in the field of electronic business and electronic trade and it has to satisfy requests and practical needs, in the first place, of businessmen whose interest is to have a legal basis they can rely on.